Study on dynamic adsorption characteristics of broken coal gangue to heavy metal ions under leaching condition and its cleaner mechanism to mine water. (20th December 2021) - Li, Junmeng; Huang, Yanli; Li, Wei; Guo, Yachao; Ouyang, Shenyang; Cao, Guolei
Abstract: The underground reservoir of a coal mine can store and purify mine water. The high salinity ions in the underground reservoir of a coal mine can be removed by the adsorption with gangue block, and the high salinity mine water can be purified in the flow process of the underground reservoir of a coal mine. Through the dynamic leaching experiments, the effects of gangue gradation, ion concentration and ion sort of displacement fluid on the dynamic adsorption characteristics of gangue were studied, the leaching laws of Ca 2+, K +, Mg 2+ ions were obtained. The results show that (1) the smaller the average particle size of the gangue in the leaching column, the better the adsorption effect of the leaching column on Ca 2+, the higher the removal rate of Ca 2+ . (2) Mg 2+ has a relatively strong promoting effect on the dissolution of K + and Ca 2+, and K + also has a relatively strong promoting effect on the dissolution of Mg 2+ . (3) The higher the concentration of Ca 2+ in the displacement fluid, the more significant the promoting effect of Ca 2+ on the dissolution of Mg 2+ and K +, and the greater the dissolution mass of Mg 2+ and K + in unit time. (4) There are two different types of adsorption sites for Ca 2+ on the surface of gangue. When the concentration is low, Ca 2+ is adsorbed by the first adsorption site. When the concentration is high, Ca 2+ is adsorbed by the second adsorption site. The research results can provide theoretical reference and data support for the in-depth understanding of the water purification mechanism and engineering design of underground reservoir in a coal mine.